An open source decision support system to improve healthcare show rates - Peixoto, Hugo (2011)
Oliveira T., Costa A., Neves J., Novais P., Digital Clinical Guidelines Modelling, Modelling and Simulation 2011, Novais P., Machado J., Analide C., Abelha A., (Eds.) (ESM’2011 – The 2011 European Simulation and Modelling Conference, Guimarães, Portugal) EUROSIS Publisher, ISBN: 978-9077381-66-3, 2011.